Beyond being the Largest Economy in Africa: An Ethical Equiry into the Major Causes and Effects of Poverty in Nigeria - Ojoajogwu, Okpe Nicholas (Advances in Social Sciences Research Journal, 2014)
The reasons for poverty could be very numerous in the like manner of the effects. Some people believe that poverty results from a lack of adequate resources on a global level; resource such as land, food, and building materials—that are necessary for the well-being or survival of the world’s people. Others see poverty as an effect of the uneven distribution of resources around the world on an international or even regional scale. It is further believed that overpopulation is another cause of poverty: This is a situation of having large numbers of people with too few resources and too little space. Excessively high population densities put stress on available resources. Only a certain number of people can be supported on a given area of land, and that number depends on how much food and other resources the land can provide. In countries where people live primarily by means of simple farming, gardening, herding, hunting, and gathering, even large areas of land can support only small numbers of people because these labor-intensive subsistence activities produce only small amounts of food. In many developing countries, the problems of poverty are massive and pervasive. Some nations have become fairly wealthy, however, lack essential raw materials and the knowledge and skills gained through formal education and training. They also often lack the infrastructure provided by, for example, transportation systems and power-generating facilities. Because these things are necessary for the development of industry, developing countries generally must rely on trade with developed countries for manufactured goods, but they cannot afford much. Nigeria was recently adjudged to be the largest economy in Africa, while the stark reality on ground does not seem to agree with this. Because of this assertion and counter assertion, this paper sets out to social ethically analyze the causes and effects of poverty in Nigeria while maintaining and proffering that those responsible for lifting people out of poverty should not be carried away by principles and theories while much leaves to be desired in imparting the lives of the common Nigeria.